A Resistência Quotidiana dos Homossexuais no Estado Novo - Afonso, Raquel (Trabalhos de Antropologia e Etnologia, 2020)
As it is known, during the 20th century, several European countries were under the power of fascists dictatorships, in which homosexuality was condemned, at the legislative, medical, religious or social level. In Portugal, although the study about homosexuality in the Salazarist dictatorship has already begun, little is known about the lesbians and gays who lived through this period, especially the lives of ordinary people. Thus, this article, which is based on my master’s thesis, it aims to reflect on homosexuality during the Estado Novo and on the life of homosexuals and lesbians during this period. The vision of homosexuality during the Salazarism is approached and the daily life of these people, who clandestinely lived their sexuality. I also analyze the forms of daily resistance that went through the concealment of homosexuality but also through the clandestine practice of it, in places identified by homosexuals as places of encounter and sexual practice.